The New Meaning of Educational Change - Fullan, Michael (Routledge, 2007)
When Michael Fullan published the first edition of this seminal work in 1982, he revolutionized the theory and practice of education reform. Now, a quarter of a century later, his new fourth edition promises to be equally influential for radical reform in the 21st Century. The New Meaning of Educational Change is your definitive compendium to all aspects of the management of educational change - a powerful resource for everyone involved in school reform.
Keywords: Education / Administration / General; Education / Educational Policy & Reform / General; Education / Leadership